THE LEGAL POSITION OF A PERPETRATOR WITNESS (JUSTICE COLLABORATOR) IN THE CRIMINAL OFFENSE OF HUMAN TRAFFICKING (TPPO) RELATED TO SEXUAL VIOLENCE UNDER THE LAW ON SEXUAL VIOLENCE CRIMES (UU TPKS) - Mochamad Galih; Yusep Mulyana (RADJA PUBLIKA, 2026)
Human Trafficking (TPPO) related to sexual violence is an extraordinary crime that is organized, has widespread impact, and causes physical suffering, psychological suffering, and economic loss for victims. In law enforcement practice, law enforcement, and uncovering human trafficking (TPPO) networks often requires the role of witnesses (justice collaborators) to uncover the involvement of the main perpetrators. Normatively, the regulation of justice collaborators in Indonesia is regulated by Law Number 31 of 2014 concerning Witness and Victim Protection and is strengthened by Supreme Court Circular Letter Number 4 of 2011. However, Law Number 12 of 2022 concerning Sexual Violence (UU TPKS) does not explicitly regulate the mechanisms, criteria, and implications of granting justice collaborator status in sexual violence cases, including those related to TPPO. This normative vacuum has the potential to lead to inconsistent decisions, legal uncertainty, and an imbalance between the interests of proof and victim protection. This research uses a normative juridical method with a statutory, conceptual, and case study approach. The analysis was conducted on the regulation of justice collaborator in the Indonesian criminal law system, the position of witnesses and perpetrators in human trafficking cases based on sexual violence according to the TPKS Law, and its implications for the principles of justice and victim protection. The results of the study indicate that the regulation of justice collaborator is still general and has not been comprehensively integrated with the TPKS legal regime. As a result, the granting of this status is highly dependent on the discretion of law enforcement officials and judges. From the perspective of criminal law policy and due process of law, the granting of justice collaborator status must still guarantee the principles of proportionality, accountability, and protection of victims' rights, including the right to restitution and victim recovery. Therefore, it is necessary to harmonize regulations between the Witness and Victim Protection Law and the TPKS Law, as well as the formulation of clear technical guidelines regarding the procedures, criteria, and limitations for granting justice collaborator status in human trafficking cases based on sexual violence. This approach is important to strengthen the integrity of the criminal justice system while ensuring that victim protection and recovery remain the primary orientation in law enforcement.